In‐line stepped ridge coaxial‐to‐rectangular waveguide transition with capacitive coupling. Issue 3 (21st December 2018) - Vincenti Gatti, Roberto; Rossi, Riccardo; Dionigi, Marco
Abstract: An original in‐line coaxial‐to‐rectangular waveguide transition including stepped ridged sections is presented. This device differs from the state of the art because of the coaxial inner conductor not being in electrical contact with the ridge, leading to considerable mechanical advantages. In addition to this, capacitive coupling can extend the bandwidth even with a few matching sections when compared with the traditional counterpart presenting DC contact with the first ridge. An ultra‐compact transition is designed, manufactured, and tested in back‐to‐back configuration. From measured data, a return loss better than 20 dB on a bandwidth of 1.27 GHz (12.2%) is observed in this configuration. An average insertion loss of 0.11 dB can be derived for the standalone transition.